Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To solve for [tex]\( a \)[/tex] and [tex]\( b \)[/tex] in the complex number division [tex]\(\frac{2 - 2i}{3 + 4i}\)[/tex], we'll follow these steps:
1. Find the conjugate of the denominator: The conjugate of [tex]\(3 + 4i\)[/tex] is [tex]\(3 - 4i\)[/tex].
2. Multiply the numerator and the denominator by the conjugate of the denominator to remove the imaginary part from the denominator:
[tex]\[ \frac{2 - 2i}{3 + 4i} \cdot \frac{3 - 4i}{3 - 4i} \][/tex]
3. Perform the multiplication in the numerator and the denominator:
[tex]\[ \text{Numerator: } (2 - 2i)(3 - 4i) \][/tex]
Applying the distributive property (FOIL method):
[tex]\[ = 2 \cdot 3 + 2 \cdot (-4i) - 2i \cdot 3 - 2i \cdot (-4i) \][/tex]
[tex]\[ = 6 - 8i - 6i + 8i^2 \][/tex]
Since [tex]\(i^2 = -1\)[/tex]:
[tex]\[ = 6 - 8i - 6i + 8(-1) \][/tex]
[tex]\[ = 6 - 8i - 6i - 8 \][/tex]
[tex]\[ = -2 - 14i \][/tex]
Now for the denominator:
[tex]\[ \text{Denominator: } (3 + 4i)(3 - 4i) \][/tex]
Applying the distributive property:
[tex]\[ = 3 \cdot 3 + 3 \cdot (-4i) + 4i \cdot 3 + 4i \cdot (-4i) \][/tex]
[tex]\[ = 9 - 12i + 12i - 16i^2 \][/tex]
Since [tex]\(i^2 = -1\)[/tex]:
[tex]\[ = 9 - 12i + 12i + 16 \][/tex]
[tex]\[ = 9 + 16 \][/tex]
[tex]\[ = 25 \][/tex]
4. Combine the results to form the final division result:
[tex]\[ \frac{-2 - 14i}{25} \][/tex]
[tex]\[ = \frac{-2}{25} + \frac{-14i}{25} \][/tex]
This gives us [tex]\(-\frac{2}{25} + -\frac{14}{25}i\)[/tex].
From this, we clearly see that [tex]\(a = -\frac{2}{25}\)[/tex].
Therefore, the value of [tex]\(a\)[/tex] is:
A) [tex]\(\frac{-2}{25}\)[/tex]
1. Find the conjugate of the denominator: The conjugate of [tex]\(3 + 4i\)[/tex] is [tex]\(3 - 4i\)[/tex].
2. Multiply the numerator and the denominator by the conjugate of the denominator to remove the imaginary part from the denominator:
[tex]\[ \frac{2 - 2i}{3 + 4i} \cdot \frac{3 - 4i}{3 - 4i} \][/tex]
3. Perform the multiplication in the numerator and the denominator:
[tex]\[ \text{Numerator: } (2 - 2i)(3 - 4i) \][/tex]
Applying the distributive property (FOIL method):
[tex]\[ = 2 \cdot 3 + 2 \cdot (-4i) - 2i \cdot 3 - 2i \cdot (-4i) \][/tex]
[tex]\[ = 6 - 8i - 6i + 8i^2 \][/tex]
Since [tex]\(i^2 = -1\)[/tex]:
[tex]\[ = 6 - 8i - 6i + 8(-1) \][/tex]
[tex]\[ = 6 - 8i - 6i - 8 \][/tex]
[tex]\[ = -2 - 14i \][/tex]
Now for the denominator:
[tex]\[ \text{Denominator: } (3 + 4i)(3 - 4i) \][/tex]
Applying the distributive property:
[tex]\[ = 3 \cdot 3 + 3 \cdot (-4i) + 4i \cdot 3 + 4i \cdot (-4i) \][/tex]
[tex]\[ = 9 - 12i + 12i - 16i^2 \][/tex]
Since [tex]\(i^2 = -1\)[/tex]:
[tex]\[ = 9 - 12i + 12i + 16 \][/tex]
[tex]\[ = 9 + 16 \][/tex]
[tex]\[ = 25 \][/tex]
4. Combine the results to form the final division result:
[tex]\[ \frac{-2 - 14i}{25} \][/tex]
[tex]\[ = \frac{-2}{25} + \frac{-14i}{25} \][/tex]
This gives us [tex]\(-\frac{2}{25} + -\frac{14}{25}i\)[/tex].
From this, we clearly see that [tex]\(a = -\frac{2}{25}\)[/tex].
Therefore, the value of [tex]\(a\)[/tex] is:
A) [tex]\(\frac{-2}{25}\)[/tex]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.